Message forwarding based on periodically evolving social characteristics in opportunistic mobile networks - Yong-feng HUANG; Yong-qiang DONG; San-feng ZHANG; Guo-xin WU (Tongxin xuebao, 2015)
To avoid monster community problem which suffered by distributed k-clique community detection, τ-window community detection was proposed. In addition, τ-window centrality estimation was put forward. By investigating the periodic evolution of τ-window community and τ-window centrality, two new metrics, TTL(time to live) community and TTL centrality, were proposed to improve the prediction of the node's encounter during the message's lifetime. Moreover, a social-aware routing algorithm, PerEvo, was then designed based on them. Extensive trace-driven simulation results show that PerEvo achieves higher message delivery ratio than the existing social-based forwarding schemes, while keep-ing similar routing overhead.